2003
DOI: 10.1308/003588403766275088
|View full text |Cite
|
Sign up to set email alerts
|

The flexor hallucis longus tendon transfer for chronic tendo-achilles ruptures revisited

Abstract: Ann R Coll Surg Engl 2003; 85is pulled partially into the umbilical port under vision, while the camera is being withdrawn. The Hassan's umbilical port is then removed and the ends of the silk are grasped with artery forceps and pulled, thereby delivering the bag to the surface of the wound (Fig. 2). The bag and its contents may then be retrieved safely leaving the wound completely protected.Discussion: Most retrieval bags have a tendency to tear or the pulling grasper may slip during extraction.2 Tying a silk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…14 Achilles tendon repair is commonly augmented with the plantaris tendon, peroneus brevis tendon, and flexor hallucis longus tendon. [4][5][6] The latter 2 have comparable mechanical properties. 15 Plantar flexors are the muscles that push off the ground during walking.…”
Section: Achilles Tendon Peroneus Brevis Discussionmentioning
confidence: 98%
“…14 Achilles tendon repair is commonly augmented with the plantaris tendon, peroneus brevis tendon, and flexor hallucis longus tendon. [4][5][6] The latter 2 have comparable mechanical properties. 15 Plantar flexors are the muscles that push off the ground during walking.…”
Section: Achilles Tendon Peroneus Brevis Discussionmentioning
confidence: 98%
“…This technique has been gradually recognized and continually improved over the years. Studies have shown that FHLT transfer is a safe and effective surgical approach for patients with chronic AT rupture [25][26][27][28]. However, the evidence of this technique is insufficient due to the limited number of reports and cases, and the lack of long term follow-up data.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, a patient sustains a rupture, but this is not diagnosed and the patient presents with a chronic rupture 4-6 weeks later [10][11][12][13][14][15]. Although there is still much controversy about how to manage acute ruptures, most surgeons agree that chronic ruptures should be treated operatively when possible, as they are associated with considerable functional morbidity [16].…”
Section: Introductionmentioning
confidence: 99%